2004
DOI: 10.1124/jpet.104.075960
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Duloxetine, a Potent and Balanced Serotonergic and Noradrenergic Reuptake Inhibitor, in Inflammatory and Acute Pain Models in Rodents

Abstract: Duloxetine, a selective but balanced serotonergic and noradrenergic reuptake inhibitor, was evaluated in the acute nociceptive pain models of tail flick and hot plate in mice and in the persistent and/or inflammatory pain models of acetic acidinduced writhing in mice, carrageenan-induced thermal hyperalgesia and mechanical allodynia in rats, and capsaicin-induced mechanical allodynia in rats. In acute pain models, duloxetine had no significant effect on response latency in the mouse tail-flick test but produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 38 publications
10
120
0
5
Order By: Relevance
“…These results suggested that inhibition of serotonin and norepinephrine reuptake involves separate pain pathways in this rat model. Similar conclusions were gleaned from the results of studies which studied the effects of duloxetine in various models of pain in the rat [41]. Thus, duloxetine, could reverse or prevent acetic acid-induced writhing and duloxetine also showed efficacy in reversing carrageenanand capsaicin-induced hyperalgesia and allodynia at doses that had limited effect on acute nociception in the tail-flick and hot plate tests with little change in normal motor function.…”
Section: Pain Pathways Targeted By Snris: Results From Experimentallysupporting
confidence: 59%
“…These results suggested that inhibition of serotonin and norepinephrine reuptake involves separate pain pathways in this rat model. Similar conclusions were gleaned from the results of studies which studied the effects of duloxetine in various models of pain in the rat [41]. Thus, duloxetine, could reverse or prevent acetic acid-induced writhing and duloxetine also showed efficacy in reversing carrageenanand capsaicin-induced hyperalgesia and allodynia at doses that had limited effect on acute nociception in the tail-flick and hot plate tests with little change in normal motor function.…”
Section: Pain Pathways Targeted By Snris: Results From Experimentallysupporting
confidence: 59%
“…The procedure followed the protocol described by Jones et al [13] . Two different hotplate temperatures, 52 °C and 55 °C, were used.…”
Section: Tail-flick Testmentioning
confidence: 99%
“…The doses of antidepressants were chosen according to previous studies (Singh et al, 2001;Iyengar et al, 2004;Jones et al, 2005) and our pilot studies, in which the drug dose that produced the maximum analgesic effect without causing toxicity or motor impairment was identified. Thermal and mechanical sensitivity and formalin-induced spontaneous nociceptive behavior were measured as mentioned above.…”
Section: Antidepressant Drugsmentioning
confidence: 99%